인구변화에 대응한 노인요양공동생활가정 공간재생을 위한 사례분석 및 사용성 평가 - 남경숙 (한국공간디자인학회 논문집, 2018)
(연구배경 및 목적) 한국의 인구 고령화 속도의 가속화와 노인 인구의 증가 추세가 갈수록 커지고 있다. 인구 고령화가 노인 인구에 대한 사회 서비스가 점차 확대되어 가고 있다. 서비스 내용과 시설 등에서 이미 점차 형태를 잡아서 자체의 특색을 형성하였다. 노인의료복지시설 대폭 증가하고 있는 것으로 보인다. 그중에 노인요양시설의 증가율보다 노인요양공동생활가정의 증가율은 더 높은 것을 나타낸다. 이에 따라 본 연구의 목적은 노인들에게 쾌적한 공동생활을 유지하기 위해 고령 인구변화에 대응한 노인요양공동생활가정의 공간재생 대한 연구를 하고자 한다. (연구방법) 본 연구의 방법은 선행연구 조사, 사례조사와 설문조사를 병행하여 연구를 진행하였다. 세부 연구 방법은 다음과 같다. 첫째, 선행연구를 통하여 노인요양공동생활가정에 관련 있는 이론적 배경 및 현황을 파악하여였고, 이를 통해 노인요양공동생활가정의 재생을 위한 공간구성과 특성을 도출하였다. 둘째, 정리된 항목을 바탕으로 사례조사를 진행하고 사용자에게 사용성에 관한 설문조사를 진행하였다. 셋째, 설문조사를 한 후에 SPSS 프로그램을 이용하여, 받은 사용서 평가를 분석하였다. (결과) 첫째, 자료에 의하여 서울시 노인요양공동생활가정 개소 상위 4위의 구역을 선정했다. 둘째, 선정된 노인요양공동생활가정의 공간에 대하여 분석했다. 셋째, 설문지 및 SPSS 프로그램을 통하여 조사결과를 분석했다. (결론) 노인요양공동생활가정은 노인들에게 요양시설이며, 동시에 동년배 노인들을 모이고, 서로 교류와 생활하는 공간이다. 따라서 건강한 시설환경과 충분한 공간면적을 확보하여 노인들의 자연스러운 소통과 생활이 이루어져야 하다. 또한 노인들의 이동이 자유로운 공간구조가 이루어지는 동시에 안전한 요소를 이루어져야 한다. 노인들이 생활하는 동안 노인에 대한 적응한 여가활동과 공간의 배치계획에 대한 고려가 필요하다. (Background and Purpose) The pace of aging in Korea is accelerating causing rapid increase in the elderly population. The elderly nursing homes have showed a higher growth rate than the elderly sanatoriums. In order to maintain a comfortable communal life for the elderly, there is a growing need to respond to the changes in the elderly population. Therefore, this research focuses on the regeneration of space for the elderly nursing homes. (Method) The methods of this study were conducted in parallel with the preceding studies, case studies, and surveys. Research methods are as follows. First, the theoretical background and status of the elderly care younger brother's house were examined through prior research; and through this, the spatial composition and characteristics necessary for the regeneration of the elderly nursing homes were derived. The spatial components were derived from the typical characteristics like stability, health, and applicability. Second, case studies were conducted based on the items organized and a questionnaire survey on usability was administered to users. Third, after the survey, the usability evaluation was analyzed using the SPSS program. (Results) First, the top four areas for the elderly nursing homes in Seoul were selected based on the Ministry of Health and Welfare's "2018 Status of Welfare Facilities for the Elderly." Second, we analyzed the space in the selected elderly nursing homes. Third, the survey results were analyzed through questionnaires and the SPSS program. The results of a one-way ANOVA that was conducted to verify differences in satisfaction between different age groups are as follows: space width, preventing slippage, removing thresholds, installing guardrails, lighting brightness, sound insulation, proper placement of instruments, and sufficient number of various types of instruments showed significant differences. Emergency bell installation and spatial cleanliness did not show any significant differences. The results of a one-way ANOVA that was conducted to verify differences in satisfaction on the basis of health condition are as follows: space width, preventing slippage, removing threshold, installing guardrails, emergency bell installation, lighting brightness, cleanliness, acoustic facilities, and sufficient equipment types showed significant differences. No significant differences in instrument position allowances were observed. (Conclusions) The older the age and health, the greater the interest in the installation of the interior space of the nursing home, and the lower the age and the healthier the installation, the less the interest and the more satisfied the installation is, the more likely it is to be necessary to carefully consider the target of age and health. An elderly nursing home is a space where elderly people gather and interact with each other. Therefore, natural communication and daily leisure activities for the elderly should be encouraged by ensuring a healthy environment and sufficiently wide spaces. The elderly nursing homes should also consist of safety elements while providing a free space for the elderly.
Keywords: 고령화; 노인요양공동생활가정; 공간재생; 인구변화; 사용성 평가; Aging; Nursing home; Space Regenerative; Population change; Usability evaluation